Field Crop Responses and Management Strategies to Mitigate Soil Salinity in Modern Agriculture: A Review - Hiba M. Alkharabsheh; Mahmoud F. Seleiman; Omar A. Hewedy; Martin L. Battaglia; Rewaa S. Jalal; Bushra A. Alhammad; Calogero Schillaci; Nawab Ali; Abdullah Al-Doss (Agronomy, 2021)
The productivity of cereal crops under salt stress limits sustainable food production and food security. Barley followed by sorghum better adapts to salinity stress, while wheat and maize are moderately adapted. However, rice is a salt-sensitive crop, and its growth and grain yield are significantly impacted by salinity stress. High soil salinity can reduce water uptake, create osmotic stress in plants and, consequently, oxidative stress. Crops have evolved different tolerance mechanisms, particularly cereals, to mitigate the stressful conditions, i.e., effluxing excessive sodium (Na+) or compartmentalizing Na+ to vacuoles. Likewise, plants activate an antioxidant defense system to detoxify apoplastic cell wall acidification and reactive oxygen species (ROS). Understanding the response of field crops to salinity stress, including their resistance mechanisms, can help breed adapted varieties with high productivity under unfavourable environmental factors. In contrast, the primary stages of seed germination are more critical to osmotic stress than the vegetative stages. However, salinity stress at the reproductive stage can also decrease crop productivity. Biotechnology approaches are being used to accelerate the development of salt-adapted crops. In addition, hormones and osmolytes application can mitigate the toxicity impact of salts in cereal crops. Therefore, we review the salinity on cereal crops physiology and production, the management strategies to cope with the harmful negative effect on cereal crops physiology and production of salt stress.